Peran Masker/Respirator dalam Pencegahan Dampak Kesehatan Paru Akibat Polusi Udara: [The Role of Mask in Preventing Pulmonary Air Pollution: A Review] - Haruyuki Dewi Faisal; Agus Dwi Susanto (Faculty of Medicine Universitas Airlangga, 2017)
Outdoor air pollution contributed harmful impact to public health. There are several respiratory disorders related to outdoor air pollution such as acute respiratory infection, lung cancer, asthma, chronic obstructive lung disease (COPD) and lung function disorder. Respirator is a personnel protective device which has role in the primary intervention step. Currently exist many types of respirators in industrial setting that have specific function to certain hazard exposure in work process. It is difficult to choose one type of respirator that can be implemented in population setting to protect against all air pollutant content. Therefore, it is relevant choosing one respirator type which has the ability to effectively filtrate one of air pollutant content that is the particulate matter. One respirator type, N95 mask has superiority in term of cost and technical use aspects for protecting particulate matter pollutant. Respirator usage effectivity in population setting is an important subject to find out more.